The mechanism of gut-lung axis in pulmonary fibrosis - Dong, Yawei; He, Lanlan; Zhu, Zhongbo; Yang, Fan; Ma, Quan; Zhang, Yanmei; Zhang, Xuhui; Liu, Xiping (Frontiers in Cellular and Infection Microbiology, 2024)
Pulmonary fibrosis (PF) is a terminal change of a lung disease that is marked by damage to alveolar epithelial cells, abnormal proliferative transformation of fibroblasts, excessive deposition of extracellular matrix (ECM), and concomitant inflammatory damage. Its characteristics include short median survival, high mortality rate, and limited treatment effectiveness. More in-depth studies on the mechanisms of PF are needed to provide better treatment options. The idea of the gut-lung axis has emerged as a result of comprehensive investigations into the microbiome, metabolome, and immune system. This theory is based on the material basis of microorganisms and their metabolites, while the gut-lung circulatory system and the shared mucosal immune system act as the connectors that facilitate the interplay between the gastrointestinal and respiratory systems. The emergence of a new view of the gut-lung axis is complementary and cross-cutting to the study of the mechanisms involved in PF and provides new ideas for its treatment. This article reviews the mechanisms involved in PF, the gut-lung axis theory, and the correlation between the two. Exploring the gut-lung axis mechanism and treatments related to PF from the perspectives of microorganisms, microbial metabolites, and the immune system. The study of the gut-lung axis and PF is still in its early stages.This review systematically summarizes the mechanisms of PF related to the gut-lung axis, providing ideas for subsequent research and treatment of related mechanisms.